Second-order Barker-Henderson perturbation theory for the phase behavior of polydisperse Morse hard-sphere mixture - Hvozd, T.V.; Kalyuzhnyi, Yu.V. (Condensed Matter Physics, 2015)
We propose an extension of the second-order Barker-Henderson perturbation theory for polydisperse hard-sphere multi-Morse mixture. To verify the accuracy of the theory, we compare its predictions for the limiting case of monodisperse system, with predictions of the very accurate reference hypernetted chain approximation. The theory is used to describe the liquid--gas phase behavior of the mixture with different type and different degree of polydispersity. In addition to the regular liquid--gas critical point, we observe the appearance of the second critical point induced by polydispersity. With polydispersity increase, the two critical points merge and finally disappear. The corresponding cloud and shadow curves are represented by the closed curves with `liquid' and `gas' branches of the cloud curve almost coinciding for higher values of polydispersity. With a further increase of polydispersity, the cloud and shadow curves shrink and finally disappear. Our results are in agreement with the results of the previous studies carried out on the qualitative van der Waals level of description.